LEGAL CERTAINTY IN PROVING VERBAL SEXUAL HARASSMENT CASES: A JURIDICAL ANALYSIS OF CRIMINAL JUSTICE SYSTEM IN INDONESIA (UUM Journal of Legal Studies, 2025)
This study explored the importance of legal certainty in addressing verbal sexual harassment and evaluating material and formal evidence of legal framework in Indonesia. The analysis also showed the need for clear and explicit laws, efficient enforcement, as well as appropriate penalties to ensure a safe and respectful environment while upholding individual rights or dignity. Focusing on the legal challenges of proving verbal sexual harassment, this socio-legal study used statutory, legal concepts, and comparative analysis to examine international as well as national laws on sexual harassment. The analysis signified the necessity of protecting fundamental rights such as freedom from discrimination and sexual harassment while addressing evidentiary challenges as well as advocating for clear legal guidelines. By analysing laws from Indonesia, India, and New Zealand, the study showed the role of technology and written records in strengthening legal certainty in verbal sexual abuse cases. Finally, the findings aimed to improve legal understanding or provide practical solutions that benefit both victims and authorities in Indonesia.